Measuring Statistical Capacity Building : A Logical Framework Approach - Morrison, Thomas; Khawaja, Sarmad (Washington, D.C. : International Monetary Fund, 2001)
This paper suggests a way forward in the effort to measure statistical capacity building by combining features of two tools - the Project Management System, a logical framework methodology that the IMF Statistics Department uses to plan, monitor, and evaluate technical assistance projects, and the Data Quality Assessment Framework, a methodology for assessing data quality that brings together best practices and internationally accepted concepts and definitions in statistics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet